Neuromyelitis optica: clinical features, immunopathogenesis and treatment - Jarius, Sven; Wildemann, Brigitte; Paul, Friedemann (Clinical & experimental immunology, 2014)
The term ‘neuromyelitis optica’ (‘Devic's syndrome’, NMO) refers to a syndrome characterized by optic neuritis and myelitis. In recent years, the condition has raised enormous interest among scientists and clinical neurologists, fuelled by the detection of a specific serum immunoglobulin (Ig)G reactivity (NMO-IgG) in up to 80% of patients with NMO. These autoantibodies were later shown to target aquaporin-4 (AQP4), the most abundant water channel in the central nervous system (CNS). Here we give an up-to-date overview of the clinical and paraclinical features, immunopathogenesis and treatment of NMO. We discuss the widening clinical spectrum of AQP4-related autoimmunity, the role of magnetic resonance imaging (MRI) and new diagnostic means such as optical coherence tomography in the diagnosis of NMO, the role of NMO-IgG, T cells and granulocytes in the pathophysiology of NMO, and outline prospects for new and emerging therapies for this rare, but often devastating condition.
Gesehen am 10.09.2020